Natural and Anthropogenic Determinants of Productivity, Emission Intensity and Environmental Efficiency of Central Asian Countries Against a Worldwide Background - Altyn Shayakhmetova; Dmitriy Il; Anargul Belgibayeva; Arkadiusz Sadowski; Natalia Genstwa-Namysł; Jagoda Zmyślona; Aigul Timurbekova; Ainagul Kaliyeva; Shynar Arynova; Irina Chidunchi; Kulbaram Bayazitova; Galiya Tumenova; et al. (Agriculture)
The study is devoted to determining the factors affecting the volume of agricultural production, the ability to meet the food needs of populations, as well as the environmental efficiency of production, defined as the ratio of the number of kilocalories produced by the agricultural sector to the amount of greenhouse gasses it emits. Central Asian countries (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan) were chosen as an example. They are characterized by similar natural conditions (mainly dry, continental climate, and the dominant role of permanent grassland in agricultural land use), as well as a common economic history (as former republics of the USSR). As shown in this study, land productivity and environmental efficiency of production depend on natural factors, while the actual ability to meet each nation’s food needs depends on human activity, including primary measures taken to improve environmental efficiency within natural limits.